2008
DOI: 10.1590/s0034-70942008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio do nervo frênico após realização de bloqueio do plexo braquial pela via interescalênica: relato de caso

Abstract: BACKGROUND AND OBJECTIVES:Phrenic nerve block is a common adverse event of brachial plexus block. However, in most cases it does not have any important clinical repercussion. The objective of this work was to report a case with phrenic nerve block with respiratory repercussions in a patient with chronic renal failure who had an extensive arteriovenous fistula created under perivascular interscalene brachial plexus block. CASE REPORT:A 50-year old male patient, smoker, with chronic renal failure on hemodialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[45] Attempts being made to reduce the side effects due to ISB have been inconsistent. [678] The occurrence of increasing number of postoperative neurological deficits where ISB method is used to give local anaesthesia has been attributed to harmful needle–nerve contact. [9] A cadaveric study concluded that difficulty with ultrasound discrimination of tissue layers may contribute to subepineurial injection in as many as 50% of intrafascial ISB procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Attempts being made to reduce the side effects due to ISB have been inconsistent. [678] The occurrence of increasing number of postoperative neurological deficits where ISB method is used to give local anaesthesia has been attributed to harmful needle–nerve contact. [9] A cadaveric study concluded that difficulty with ultrasound discrimination of tissue layers may contribute to subepineurial injection in as many as 50% of intrafascial ISB procedures.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially common adverse effect is Horner syndrome, caused by the propagation of the anesthetic drug through the cervical sympathetic trunk, and hoarseness, caused by recurrent laryngeal nerve block. Bilateral block is avoided due to risk of phrenic nerves block, which may result in bilateral palsy of the diaphragm and in ventilatory intercurrences 12 . Life-threatening complications are usually caused by inadvertent anesthetic injection in nearby arteries (subclavian and vertebral arteries) or Total spinal anesthesia after stellate ganglion block in complex regional pain syndrome patient.…”
Section: Discussionmentioning
confidence: 99%
“…1 The procedure is associated with significant postoperative pain and effective analgesia is required for successful day-case surgery. 2,3 Although ISB, 4 and more particularly continuous interscalene catheter block, is considered to be the most effective analgesic technique for ARCR, 5 it is frequently associated with phrenic nerve block, 6,7 even with the use of ultrasound and low volumes of local anaesthetic. 8 The difficulties in implementing and monitoring a perineural catheter at home have led to many anaesthesiologists to choose a single injection technique so that patients can be discharged on the same day as surgery with a satisfactory level of pain control.…”
Section: Introductionmentioning
confidence: 99%